Implementation Of Religious Character Planting Of Low Grade Elementary School Students Learning In Islamic Elementary School In Purwokerto City - Kurniawan, Alfi Muklis; Samsudi, Samsudi; Alimah, Siti (Educational Management, 2019)
The purpose of this research to analyze the internalization process of religious character conducted by teachers in the learning process in low class in Islamic elementary school in Purwokerto City. The type of research used is qualitative. Research Data is derived from interviews, observations, and documentation. The data analysis used in this research by triangulation. The results showed that the process of planting religious character in the implementation of learning carried out by associating the value of religious characters into the learning theme integrated in syllabus and RPP and applied in Implementation of learning. Research conclusion shows that the implementation of religious character planting in the low class in the implementation of learning in the city of Purwokerto carried out by integrating religious character book into the implementation of learning. The suggestions presented in this study are necessary to be further developed in subsequent studies.